The Role and Persistence of Islamic Boarding School Teachers - Subarno, Anton (LPPM Undiksha, 2024)
The Indonesian government is responsible for the education of children up to grade nine under the age of 18. The government organizes open junior high schools (SMPT) to educate children who cannot attend due to economic and geographical reasons. SMPT is implemented in disadvantaged areas through Islamic Boarding Schools (PonPes). The role and persistence of teachers at PonPes arehas yet to be discovered and appreciated as professional teachers. This research aims to analyze the role and persistence of Islamic boarding school teachers. This research is a qualitative method with an ethnographic approach. This research aims to determine the role and persistence of teachers at PonPes. Teachers, school officials, school committees, tutors, parents and school principals were involved in this research. The subjects involved in this research as key informants were school principals. Purposive snowball sampling was used to select relevant informants and data sources. Source triangulation and method triangulation were used to validate the data. Data analysis refers to the interactive data analysis model from Milles and Huberman. The research results show that teachers have three roles: character builder, diversity teacher, and encourager of students. The persistence of IBS teachers can be seen from the teachers' efforts to understand the culture and demographic characteristics of students, which can manifest in the form of behaviour as coordinators, administrators and motivators. The research implications show that teachers serve parents and students who need school information.